The Challenge of Predicting the Security Situation in Indonesia: Implementation of the Noken System in Papua - Pure, Solihin; Suryo, Almuchalif; Timur, Fauzia G Cempaka (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
The implementation of elections in Papua always has its own dynamics, one of which is the existence of the noken system. This system is a tangible recognition of the political and legal rights of the indigenous people of Papua, as guaranteed by the constitution, and has even received legal legitimacy through Constitutional Court Decision No. 47-81/PHPU.A-VII/2009, further reinforced by Constitutional Court Decision No. 06-32/PHPU-DPD/XII/2014. Noken refers to a traditional bag made by the Papuan people. This study aims to identify and analyze the challenges in predicting security situations in electoral districts with the noken system. The results of this study are expected to provide insights and recommendations for stakeholders in managing a safe and peaceful election process. This study uses a qualitative approach with a descriptive analysis method. Data sources include scientific journals, books, and articles relevant to the research topic. The full noken system is still in use in six districts in Central Papua Province: Puncak Jaya, Puncak, Paniai, Intan Jaya, Deiyai, and Dogiyai. The full and mixed Noken systems implemented in the Papua Pegunungan Province, namely Nduga Regency (Full Noken System) and Jayawijaya, Yahukimo, Mamberamo Tengah, Lanny Jaya, and Tolikara, use a mixed system in several districts and villages. The Noken system, although considered a form of local democracy in Papua, faces significant challenges in predicting security situations in electoral districts. The main challenges include limited oversight, potential communal conflicts, and a lack of transparency. To address these challenges, it is necessary to enhance the transparency of the electoral process, encourage active community participation, and foster close collaboration among stakeholders to maintain security stability in electoral districts using the Noken system.